Comparative study of the pharmacopeial quality and dissolution profiles of generic and other drug forms of sodium metamizole (dipyrone) sold in Brazil - Morenna Alana Giordani; Eduardo Borges de Melo (São Paulo State University (UNESP), 2012)
In Brazil, in order for a pharmaceutical company to register a drug form as generic or 'similar' with the Brazilian food and drug agency (Anvisa), it must be proved bioequivalent to its innovatory branded form (reference drug). This requires comparative trials, carried out in conformity with official compendia (Brazilian Pharmacopeia or another officially recognized code). Additionally, according to the Anvisa resolution RDC 31/2010, the dissolution profile of the drug must be tested and compared with that of the branded reference, as a benchmark of quality. The aim of this study was to assess the quality of 500 mg sodium metamizole (dipyrone) tablets produced by seven different laboratories in Brazil: three generic drugs (G1, G2, G3), three (branded) similar drugs (S1, S2, S 3) and their reference branded product (Novalgina®, Sanofi-Aventis, drug R). All tests were carried out by methods specified in the Brazilian Pharmacopeia 4th edition (Farmacopeia Brasileira IV). The following tests were performed: uniformity of mass, friability, disintegration time, hardness, assay, uniformity of dosage units, salicylic acid limit assay, dissolution and identification. The dissolution profile was also recorded, as recommended in RDC 31/2010. Whereas every sample was approved in all the Farmacopeia Brasileira IV tests, the results in the dissolution profile test showed that four of the test drugs (G1, G2, S1 and S2) were not pharmaceutically equivalent to drug R. Thus, only drugs G3 and S3 showed dissolution profiles similar to that of drug R and the other four drugs could not be considered equivalent to it and were not approved.